Nonpharmacist Health Care Providers' Knowledge of and Opinions Regarding Medication Costs in Critically Ill Patients. (June 2018) - Hammond, Drayton A.; Chiu, Tiffany; Painter, Jacob T.; Meena, Nikhil
Purpose: Medication cost is frequently overlooked when treating critically ill patients. Stewardship of health care resources in high-utilization settings is imperative. This study was conducted to determine nonpharmacist health care providers' knowledge and perceptions of medication costs in a medical intensive care unit (MICU).Methods: Nonpharmacist health care providers in a MICU completed a 27-item survey. The survey queried perceptions regarding medication cost, cost-limiting strategies, and most/least expensive medications in 8 classes, medication price ranges, and intravenous-to-oral comparisons for commonly prescribed medications. Responses were analyzed using descriptive statistics and compared between providers using Fisher exact tests.Results: Among 98 health care providers (76 medical trainees, 5 attending physicians, 17 nurses), when ordering a medication, 49% consider its cost. Few (15%) providers considered themselves knowledgeable regarding medication costs with no difference between providers ( P = .174). Attending physicians were more aware of the most/least expensive medications than residents (correct out of 16: 9.6 vs 8.5, P = .044). The correct price ranges for select medications (11%-36%, P = .373) and intravenous-to-oral relative costs (3%-49%, P = .596) were similarly low. Most (59%) believed pharmacists limit expensive medication use, particularly senior physicians (58% resident vs 100% attending, P = .007).Conclusion: In spite of a goal of cost consideration, most nonpharmacist health care providers are unaware of medication costs and fail to include them in decision making. These knowledge gaps and perceptions should inform future efforts to improve knowledge and attitudes regarding medication costs.